PHONETICS IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE - Marina N Shutova; Irina A Orekhova (Russian Language Studies, 2018)
The article is devoted to teaching foreign students Russian phonetics in modern system of education, problems of learning Russian sounds considering interference of the students’ native languages. The authors pay special attention to electronic phonetic courses, especially nationally oriented; games for teaching phonetics; integrated system of teaching phonetics at all levels of learning, techniques in teaching Russian pronunciation and stress. Perspectives and problems of developing phonetics are discussed in the article.